Importance of Hardening Effect and Its Analysis on Diametrical Fractured Ends of Tensile Testing of Al and Steel. (15th July 2022) - Ponnusamy, Muruganantham; Pungaiah, S. Suresh; Prabhu, M. Senthil; Ramji, B. R.; Srinivas, Y.; Periyasamy, Selvakumar
Abstract : The hardening effect varies deliberately to elevate the properties of alloy specimens either in ferrous or nonferrous materials. The cup and cone fracture theory explains the effect of hardening through heat treatment of the specimen. The hardening effects are imposed on the specimen by the furnace heating and hot pressing method. The neck formation and the elongation levels are evaluated and compared for both heat-treated and non-heat-treated specimens of steel and aluminum alloys. The simulation tools are used to predict the compressive and elongation levels by obtaining the stresses and deflections at various nodal points. The suitable heat treatment was indicated by the single or twice method of heat adoption over the steel and aluminum specimens. The fracture analysis and experimental results are compared among the hardened or non-heat-treated specimens.